(3GdGJLGg GdYdeGfj GdeYGUQ aj Ydhe GdbQBf (B:s (3OQGSI hfbO (B/s - (3GdaGVd, CMeO eMeOs ((3YeGf , GdCQOf (B:s (3OGQ GdaJM ddOQGSGJ hGdfTQ,s, 2017)
(3GSJYQV GdHGMK aj CWQhMJg eaghe GdYdeGfjI heaghe GdhMj hGdfHhI YfO GdYdeGfjjf hJGQjN YfO CMcGe GdbQBf(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI Ce OQeGf GdESdGejI, cdjI CUhd GdOjf, bSe GdJaSjQ hYdhe GdbQBf, (B2006.s
Keywords: (3GdbQBfs -- (3Ydhes; (3GdbQBf hGdYdeGfjIs